A parametric study on seakeeping assessment of fast ships in conceptual design stage - Ozum, Sadik; Sener, Bekir; Yilmaz, Huseyin (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The paper presents an approach to investigate the effects of some parameters on seakeeping assessment of fast ships in conceptual design stage. Hull form parameters have been classified into two groups: main dimensions (L, B and T) and secondary form parameters (LCB and C(p)). To demonstrate the approach a fast ship is redesigned as parent hull and alternative hull forms are generated by changing these parameters systematically. Some hull forms are selected related the geometric limits and seakeeping analyzes are here investigated and discussed. The obtained results are satisfactory for seakeeping predictions during the conceptual design stage. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Seakeeping; Fast ships; Ship motion; Engineering; Oceanography